The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10753-015-0253-7
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate Mitigates Lipopolysaccharide-Induced CD14 and TREM-1 Expression, NF-κB Activation, and Pro-inflammatory Cytokine Production in Rat Macrophages

Abstract: This study was aimed at investigating the effect of etomidate on the viability of rat macrophages and the function of lipopolysaccharide (LPS)-stimulated macrophages as well as the potential mechanisms. Rat macrophages were isolated and treated with different doses of etomidate for 24 h, and their viability was determined by the CCK-8 assay. Furthermore, macrophages were treated with, or without, 1 μg/ml of LPS, and/or 2.5 or 5 μM etomidate in the presence or absence of a TREM-1 inhibitor (LP17, 100 ng/ml), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…When TLR4 is activated by LPS, inflammatory cytokines, such as IL-6, TNF-α, IL-1β, and NF-κB, upregulate the expression of TREM1. TREM1 then augments the TLR4-mediated inflammatory response by binding with DAP12 [57,58]. The pro-inflammatory function is dependent on MAPK and NF-κB signaling pathways, and cytosolic adaptor caspase recruitment domain family member 9 (CARD9) plays an important role in promoting inflammation [71].…”
Section: Mechanism Of Trem In Inflammationmentioning
confidence: 99%
“…When TLR4 is activated by LPS, inflammatory cytokines, such as IL-6, TNF-α, IL-1β, and NF-κB, upregulate the expression of TREM1. TREM1 then augments the TLR4-mediated inflammatory response by binding with DAP12 [57,58]. The pro-inflammatory function is dependent on MAPK and NF-κB signaling pathways, and cytosolic adaptor caspase recruitment domain family member 9 (CARD9) plays an important role in promoting inflammation [71].…”
Section: Mechanism Of Trem In Inflammationmentioning
confidence: 99%
“…The lowest expression levels in Dex-Eto group indicated that compared with the simple treatment with dexmedetomidine alone, dexmedetomidine combined with etomidate had more significant inhibition on inflammatory cytokines. In the study of Wang et al (4), dexmedetomidine was reported to be able to reduce TNF-α, IL-6, IL-1β and other expression levels, and thus reduce inflammation; whereas Liu et al (18) reported that etomidate could inhibit the production of pro-inflammatory cytokines in rat macrophages, so dexmedetomidine and etomidate may play a joint role in downregulating TNF-α, IL-6 and IL-1β without eliminating each other.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, the expression of NF-κB p65 in the hippocampus of each group was studied, and the results indicated that the expression of NF-κB p65 was increased in the hippocampus of aged rats with POCD in Morris water maze test, but decreased after drug treatment, with that of the Dex-Eto group being the lowest. This may be due to the fact that dexmedetomidine and etomidate co-inhibit NF-κB in order to alleviate inflammation (18,30), with no elimination effect on each other. In addition, by analyzing the correlation of the above factors, it was shown that the decrease of IL-17A and S-100β may cause the decrease of NF-κB p65, TNF-α, IL-6 and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have investigated the effect of etomidate on cancer. In one study in vivo , etomidate was found to reduce the viability of macrophages significantly, in a dose-dependent manner [ 46 ]. In a clinical study, they found etomidate had less effect on immune function in patients with lung adenocarcinoma than propofol [ 47 ].…”
Section: The Effect Of Intravenous Agents On Cancersmentioning
confidence: 99%